The Influence Of CAR, FDR, BOPO, And TPF on the Profitability of Islamic Commercial Bank in Indonesia in the 2016-2020 Periode - Annisa Rakhmawati Respati Ningsih; Nana Diana (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
This study aims to determine the effect of CAR, FDR, BOPO, and TPF on the profitability (proxied by return on assets) of Islamic commercial banks in Indonesia in the 2016-2020 period . Data analysis in this study used a quantitative descriptive method. Data collection uses secondary data using a purposive sampling technique. The population is Islamic commercial banks in Indonesia and took 7 Islamic commercial banks to be used as samples. The sample has been tested using the classical assumption test and the analytical method used is multiple linear regression analysis . The results showed that the independent variables, namely CAR, FDR, BOPO, and TPF simultaneously had a significant effect on the dependent variable, namely ROA of 82.3%. While partially, the BOPO variable has no significant effect on ROA, while the CAR, FDR, and DPK variables have no effect on ROA.